The promise of Fintech in emerging markets: Not as disruptive - Tatiana Zalan; Elissar Toufaily (Contemporary Economics, 2017)
Fintech innovations - innovations by financial services providers based on digital technology - are widely believed to have a disruptive effect on the financial services industry. The purpose of the paper is to investigate how financial services industry participants perceive the effect of digital disruption as well as to explore what strategies are being adopted by incumbents in the face of potential disruption from fintech challengers. Based on an exploratory study with stakeholders from the financial ecosystem in the Middle East and North Africa (MENA), the findings show that the fintech sector is still nascent, but is likely to be disruptive in selected product and customer segments. Multiple regulatory, structural, and cultural obstacles stand in the way of fintech adoption. Incumbents' preferred strategy to face the future disruption is the bank-fintech collaboration, which will create new value for ecosystem partners and speed up innovation. Our study adds useful insights to the body of knowledge related to disruptive innovations in general and fintech in emerging markets in particular. Specifically, the collaborative response is inconsistent with the strategies usually recommended for incumbents in disruptive innovation theory. We hypothesize that our participants' preference for partnering can be explained in the light of the distinctive characteristics of the digital economy. We propose a framework for creating a financial services platform embedded in a broader ecosystem to facilitate the bank-fintech collaboration.
Keywords: G21; G23; L1; 330; disruptive innovation; fintech; financial services industry; emerging markets; banks